(untitled) (Archive of Conferences, 2021)
The beloved national poet Muhammad Yusuf, who captured the hearts of thousands of fans with his sincere and popular lines in the sky of Uzbek poetry, left a rich literary legacy in his short life. His work reflects the high human dignity, along with the delicate manifestations of childish joy, passion and love, national simplicity, kindness, pure and unique feelings and experiences. Effective use of the artistic potential of each word, musical smoothness, purity of feelings, sincerity and love, a clear expression of spiritual experiences are the leading features of Muhammad Yusuf’s poetic style. There is no one in Uzbekistan who did not know M. Yusuf, did not hear about him, did not recite his poems, did not sing his songs